(NuPRAWLENIE W RUSSKOM QZYKE (B:s (NsLOWARX(B-(NSPRAWO^NIK (B: (NdLQ RABOTNIKOW PE^ATI (B/s - (NrOZENTALX(B, (NdITMAR |LXQ[EWI^s ((NmOSKWA (B:s (NkNIGA(B,s, 1981)
(NpREDM(B. (NUKAZ(B.: (NSTR(B. 258-299s
Keywords: (NkNIGOWEDENIEs; (NsLOWARI RUSSKOGO QZYKAs; (NuPRAWLENIE W RUSSKOM QZYKEs